Inoculation With Azospirillum spp. Acts as the Liming Source for Improving Growth and Nitrogen Use Efficiency of Potato - Naqqash, Tahir; Malik, Kauser Abdullah; Imran, Asma; Hameed, Sohail; Shahid, Muhammad; Hanif, Muhammad Kashif; Majeed, Afshan; Iqbal, Muhammad Javed; Qaisrani, Muther Mansoor; van Elsas, Jan Dirk (Frontiers in Plant Science, 2022)
Nitrogen (N) is one of the limiting factors for plant growth, and it is mainly supplied exogenously by fertilizer application. It is well documented that diazotrophic rhizobacteria improve plant growth by fixing atmospheric N in the soil. The present study investigates the nitrogen-fixing potential of two Azospirillum spp. strains using the 15N isotope-dilution method. The two diazotrophic strains (TN03 and TN09) native to the rhizosphere of potato belong to the genus Azospirillum (16S rRNA gene accession numbers LN833443 and LN833448, respectively). Both strains were able to grow on an N-free medium with N-fixation potential (138–143 nmol mg−1 protein h−1) and contained the nifH gene. Strain TN03 showed highest indole acetic acid (IAA) production (30.43 μg/mL), while TN09 showed highest phosphate solubilization activity (249.38 μg/mL) while both diazotrophs showed the production of organic acids. A 15N dilution experiment was conducted with different fertilizer inputs to evaluate the N-fixing potential of both diazotrophs in pots. The results showed that plant growth parameters and N contents increased significantly by the inoculations. Moreover, reduced 15N enrichment was found compared to uninoculated controls that received similar N fertilizer levels. This validates the occurrence of N-fixation through isotopic dilution. Strain TN09 showed higher N-fixing potential than TN03 and the uninoculated controls. Inoculation with either strain also showed a remarkable increase in plant growth under field conditions. Thus, there were remarkable increases in N use efficiency, N uptake and N utilization levels. Confocal laser scanning and transmission electron microscopy showed that TN03 is an ectophyte, i.e., present outside root cells or within the grooves of root hairs, while TN09 is an endophyte, i.e., present within root cells, forming a strong association withroot it. This study confirms that diazotrophic Azospirillum spp. added to potato systems can improve plant growth and N use efficiency, opening avenues for improvement of potato crop growth with reduced input of N fertilizer.